Inclusion of Isomers/Astromers in s-process Nucleosynthesis: The Pivotal Case of 85Kr - Jaad A. Tannous; G. Wendell Misch; Matthew R. Mumpower; Bradley S. Meyer; F. X. Timmes; Aaron Couture; Chris L. Fryer (The Astrophysical Journal)
^85 Kr is an s -process branch point nucleus: the competition between neutron capture and β decay influences the production of nearby nuclides. Its evolution is complicated by the existence of a long-lived isomer that β -decays on a much shorter timescale than the ground state. We calculate the effective thermal transition rates between the ground and isomeric states along with estimates of their thermal β -decay rates in a suite of nucleosynthesis computations to assess the consequences of this isomer on isotopic abundances. A central finding in this study is that the s -process flow with the isomer included under astrophysical conditions relevant for the s -process creates a shift in abundance yield of the important radioactivity ^87 Rb by a factor of ∼2.4 relative to the case when the ^85 Kr is taken to be internally equilibrated when neutron exposures approach the main branch limit. On the other hand, the ^88 Sr/ ^86 Sr ratio is little affected because the bulk of the flow through ^85 Kr is still via beta decay, whether the isomer is taken into account or not.